2020
DOI: 10.1021/acs.jpcc.9b11787
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects on the Thermal Decomposition of Phosphate Esters on Ferrous Surfaces

Abstract: Phosphate esters have a wide range of industrial applications, for example in tribology where they are used as vapour phase lubricants and antiwear additives. An atomic-level understanding of phosphate ester tribofilm formation mechanisms is required to improve their tribological performance. A process of particular interest is the thermal decomposition of phosphate esters on steel surfaces, since this initiates polyphosphate film formation. In this study, reactive force field (ReaxFF) molecular dynamics (MD) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 103 publications
6
47
0
Order By: Relevance
“…Atomic interactions were modeled using the ReaxFF 33 force field with a parameter set previously developed for Fe/P/O/C/H. This parameter set has been shown to accurately reproduce P and PO adsorption energies on Fe(001) 19 as well as the adsorption and dissociation energies of intact and dissociated tri(n-butyl)phosphate on α-Fe(100) 18 by comparison to energies calculated using DFT. All simulations were run using the large-scale atomic/molecular massively parallel simulator (LAMMPS) 34 with a time step of 0.25 fs.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic interactions were modeled using the ReaxFF 33 force field with a parameter set previously developed for Fe/P/O/C/H. This parameter set has been shown to accurately reproduce P and PO adsorption energies on Fe(001) 19 as well as the adsorption and dissociation energies of intact and dissociated tri(n-butyl)phosphate on α-Fe(100) 18 by comparison to energies calculated using DFT. All simulations were run using the large-scale atomic/molecular massively parallel simulator (LAMMPS) 34 with a time step of 0.25 fs.…”
Section: ■ Methodsmentioning
confidence: 99%
“…This result, which was consistent with the experimental observation of more reactivity on iron oxide, 8 was explained by the need for oxygen atoms on the surface to enable P−O scission via nucleophilic substitution. 18 Other reactive MD simulations of thermal decomposition of TCP on Fe 3 O 4 −OH showed that the dominant reaction pathway involved Fe−C bonding. 19 These reactions were then shown to be accelerated by the presence of nanodiamonds on the surface in both simulations and quartz crystal microbalance experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical bonding information was output every 1.0 ps, using a bond order cutoff of 0.3 to identify covalent bonds . The choice of bond order cutoff only affects the postprocessing analysis and does not influence the ReaxFF energy or force calculations. , …”
Section: Methodsmentioning
confidence: 99%
“…Under the load of 1 and 2 GPa, tribochemical reaction occurs by forming multiple C–O S chemical bonds between the alcohol and the SiO 2 surface, making the molecule distorted . Ewen et al investigated the thermal decomposition of phosphate esters on ferrous surfaces. The result indicated that thermal decomposition rates were much higher on Fe 3 O 4 (001) and α-Fe(110) than on the hydroxylated, amorphous Fe 3 O 4 surface.…”
Section: Tribochemical Reactions By MD Simulationsmentioning
confidence: 99%